ANALISIS NILAI SOSIAL DALAM CERPEN SORE KERIKA ANGIN LAUT UTARA MEMANGGIL KARYA ANNISA MOEZHA - Ayu, Dwi Kusuma; Wakhyudi, Yukhsan (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This study aims to analyze the social values contained in the short story Sore Ketika Angin Laut Utara Memanggil by Annisa Moezha using a literary sociology approach. The short story portrays various aspects of the social life of coastal communities through its main character, Muzayyin. The research method used is descriptive qualitative with data collection techniques consisting of reading and note-taking. The findings show that the short story contains three main categories of social values according to Zubaedi: (1) compassion, (2) responsibility, and (3) harmony in life. Muzayyin is depicted as a figure who strongly upholds these values, although in the end, he succumbs to social and economic pressures. This short story not only conveys the social realities of village life but also reflects a shift in values due to changing times. The findings affirm the important role of literature as a medium for social criticism and a preserver of humanitarian values.